The Role of Human Resource Management Strategy in Creating Superior Quality Educators - Subianto Karoso; Warih Handayaningrum; Enie Wahyuning Handayani; Setyo Yanuarti (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2024)
This research is motivated by the urgent need for schools to have competent and superior human resources (HR) to support the success of education. HR management is strategically related to individuals' contribution to achieving academic goals. The quality of human resources in schools is essential in determining the quality of education and achieving national standards. This research aims to understand the role of human resource management in creating superior human resources in schools. The method used is a Systematic Literature Review (SLR) to analyze 30 nationally accredited articles from Google Scholar. SLR was chosen because it can provide a comprehensive picture and synthesize various relevant research results, resulting in more valid and reliable conclusions. The study results show that human resource management is central to creating quality education personnel through administrative management and teacher recruitment and selection, professional development, performance evaluation, welfare, fair compensation, school culture development, and conflict management. All of these aspects support each other in building superior human resources, ultimately improving the quality of education. This study contributes significantly to understanding the importance of HR management in the educational environment. It offers best practices that schools can apply to improve the quality of education personnel.